Can a drunk patient give informed consent for medical treatment? - Kocańda, Kamila; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2019)
When medical intervention is necessary, a physician faces a serious dilemma: can he/she perform medical intervention despite the lack of informed consent, or should he/she withdraw from such an intervention? The question is even more difficult when a patient under the influence of alcohol urgently requires a medical intervention. In such cases the possibility to gain informed consent is even more problematic, and such situations are not so rare. In such situations, a doctor must often decide whether to undertake medical interventions despite the lack of informed consent of a patient, if it is justified by patient’s state of health, or to discontinue intervention, exposing him/herself to possible legal liability for such an omission.